Areas of health-education of physicians and nurses in care for cardiac patients from the perspective of citizens of the Czech Republic - Olišarová, Věra; Šedová, Lenka; Tóthová, Valérie; Bártlová, Sylva; Chloubová, Iva; Michálková, Helena; Prokešová, Radka; Trešlová, Marie (Maghira and Maaspublications, 2016)
OBJECTIVES: The goal of this article was to assess the delivery of patient health-education, relative to cardiovascular disease from the perspective of physicians and nurses, as well as from the perspective of citizens living in the Czech Republic. METHODS: The article is based on data acquired from the “Intervention procedures in preventive cardiology” grant project. To evaluate patient health education, non-standardized questionnaires intended for physicians (n=1000) and nurses (n=1000) were used. A combination of a non-standardized questionnaire and a standardized questionnaire (SF-36) was used to assess citizen (n=1992) viewpoints. The actual investigation took place from April 1 to April 20, 2016 and was implemented over the entirety of the Czech Republic. Data were analyzed using the SASD v. 1.4.12 program. Both first and second degree sorting was used. The degree of dependence of selected characteristics was established based on the Chi-square test and the T-test. RESULTS: A bit more than half (53.1%) of the physicians indicated that nurses carried out patient education regarding influenceable risk factors associated with cardiovascular diseases, while 71.6% of nurses reported carrying out this duty. The overwhelming majority of physicians (97.1%) and nurses (92.3%) report informing patients about how to improve their health condition. Citizen respondents reported that topics such as nutrition, exercise, smoking cessation, stress reduction, and the drug side effects use were discussed with them more frequently by physicians than by nurses. Citizen respondents reported that nutrition was discussed most frequently with them, while the issue of smoking cessation was discussed the least frequently.
Oblasti zdravotně výchovného působení lékařů a sester v péči o kardiaky z pohledu občanů České republiky
Keywords: health-educational actions; education; physician; nurse; zdravotně výchovné působení - edukace – lékař – sestra